Analysis of Sports Brand Positioning Based on Consumer Perceptions - Raissa, Adina; Adhilla, Siti; Siregar, Raymond; Rahayu, Fatik (BUDGETING : Journal of Business, Management and Accounting, 2024)
The sports industry's expansion and growing focus on physical activities and healthy lifestyles have made sports brands important in satisfying consumer demands. Comprehending the positioning of sports brands in the Indonesian market is vital for formulating efficient marketing tactics and achieving a competitive advantage. This study examines various aspects of sports brand positioning, such as brand differentiation, market segmentation, brand objectives, and communication strategies. This study offers insights into the effective positioning strategies and best practices of leading sports brands in Indonesia. In the Indonesian market, comprehending the positioning strategies of sports brands is essential for gaining a competitive advantage. This study examines how selected variables enable brands to differentiate themselves and adapt to changing demands and preferences of Indonesian consumers. Consumer data is gathered via surveys and interviews. This study analyzes the brand positioning strategies of Nike, Adidas, Puma, NB, and Skechers, in relation to specific measurement variables. This study illuminates the positioning strategies utilized by selected sports brands in Indonesia. The study emphasizes the importance of various factors, including price, material quality, durability, style, brand reputation, customization options, and sustainability initiatives, in shaping consumers' perception and brand preference. This research offers valuable insights for sports marketing practitioners, brand managers, and strategic decision-makers regarding the significance of sports brand positioning and its role in achieving competitive advantages. This study adds to the current knowledge base and provides practical implications for creating effective marketing strategies in the Indonesian sports market by identifying successful positioning strategies used by these brands. Keywords: Consumer Perceptions, Sports Brand Positioning.